Women's right to access family planning and maternal health care services in Hwange rural district, Zimbabwe: challenges and opportunities - Sithole, Linet (Department of Private Law, 2021)
The significance of reproductive health and rights cannot be overemphasised. Investment in the rights of rural women, specifically their reproductive health rights, is a fundamental determinant of their empowerment and social development. Access to reproductive health services enables rural women to make informed choices in their reproductive lives. This is of paramount significance because the exercise of choice in one domain opens possibilities for choices in others. International and regional human rights treaties recognise the significance of reproductive health rights for women's wellbeing and survival and require that State Parties provide access to reproductive health services. Zimbabwe has ratified the relevant human rights treaties and has domesticated many of their provisions through the Constitution and other laws. Zimbabwe has obligations to respect, protect, promote and fulfil the right to reproductive health. Despite these obligations, rural women face a plethora of challenges in accessing reproductive health services, and their right to reproductive health continues to be infringed. The infringement is in violation of Zimbabwe's international and domestic human rights obligations. The purpose of this study was to examine and establish the challenges confronting rural women when accessing reproductive health care services in Hwange Rural District Zimbabwe. Using a phenomenology qualitative research design, data were gathered through structured face-to-face interviews with 20 women of reproductive age and five health care providers. Data from the field were bolstered with reviews of extant literature. Collected field data were thematically analysed and presented. The research findings revealed that although most of Zimbabwe's legislative, policy and institutional frameworks have provisions that comply with international obligations, the frameworks also contain restrictive provisions which perpetuate the challenges women face in accessing reproductive health care services. Furthermore, the human-rights compliant legislative and policy frameworks are often not properly implemented, thus leading to a violation of the right to reproductive health in practice. The study's empirical research revealed that in Hwange Rural District, women's capabilities to exercise their reproductive rights are limited by factors such as physical barriers like distance to the nearest health facility, availability of services, quality of care given at health facilities, poverty, religion and patriarchal tradition. A major challenge unearthed by the study was that rural women in Hwange District are not aware of their reproductive health rights. This lack of knowledge is disempowering because women who do not know their rights are not knowledgeable enough to demand their rights or defend them when violated. To redress the challenges faced by rural women, the study found that women can use judicial and extra judicial mechanisms ─ including the courts, human rights institutions, nongovernmental organisations, and civil society organisations ─ for litigation, exertion of political pressure, awareness raising and grassroots mobilisation. Such strategies are essential for ensuring that women hold the State accountable for violations of their reproductive rights. The study concludes that there is need to raise awareness on the right to reproductive health and the enacted laws and policies so as to equip women with the necessary information that will allow them to exercise their rights. It recommends that intensive human rights education programmes for both the formal and informal sector should be prioritised. It recommends the provision of adequate resourcing of various state institutions responsible for women's rights issues. Further, there should be a situational analysis of challenges faced by rural women in Zimbabwe based on the intricate factors of location within rural areas, religion, gender, human rights knowledge, culture and tradition. After such situational analysis, there is need to enact laws and policies that respond directly to the unique challenges faced by rural women, without using a ‘one size fits all' approach.